Towards Improving South Africa’s Legislation On Tax Evasion: A Comparison Of Legislation On Tax Evasion Of The USA, UK, Australia And South Africa - Storm, Ansia; Coetzee, Karina (Journal of Applied Business Research, 2017)
The fight against tax evasion in South Africa is an ongoing battle. The tools available to law enforcement boil down to legislation and the enforcement thereof. The purpose of the study that was done for this article was to compare available legislation of the United States of America, United Kingdom, Australia and South Africa to determine if South Africa’s legislation can be improved. This was done by studying the relevant literature and legislation of all four countries. The findings, that there is some clauses that can be added to improve South Africa’s legislation, were confirmed by analyzing the legislation available. In theory, the results have proven that although South Africa’s legislation can compete with that of the United States of America, United Kingdom and Australia, there is some improvement that can be considered. This is of value to the individuals and professionals who deal with the offence of tax evasion on a daily basis, ensuring that the reviewed legislation will deter perpetrators or that the charges brought against them in the court of law will ensure harsher punishment.